O conhecimento de Hanseniase entre estudantes de escolas públicas: conceitos e preconceitos - Débora Gabriele Tolentino Alves (2020)
Compulsory isolation for leprosy treatment has resulted the old colonies areas and around them. They are important areas from an epidemiological and historical point of view because they have a high prevalence of the disease and have people who have lived the isolation’s and stigma’s consequences. This study proposed to analyze the database, the result of health education and leprosy prevention activities, carried out in public schools in the region of a former leprosy colony in Betim / MG. The objective was to assess knowledge / information and perception / feeling about leprosy among students. For data analysis, descriptive statistics were used and the data were discussed based on the current disease epidemiology and on psychoanalysis concepts. It was evaluated the data obtained from 325 students aged between 10 and 19 years old, from a total of 909 registered students in both schools. Regarding knowledge, from the total number of students, 69.8% had heard about the disease and, among them, 67.8% believed that it would be curable, 11.5% knew its cause, 31.3% believed it was contagious, 57.7% knew its signs and symptoms. Among those who have never heard about leprosy, these percentages were, respectively, 59.1%, 3%, 30.3% and 24.7%. Regarding feelings, the percentage of blank responses among those who have never heard of the disease was very high, reaching more than 90% on some questions. For those who have heard of it, there were feelings of anguish / fear or altruism. Knowledge index built from the answers to the question “Have you heard of leprosy?” showed that less knowledge was related to the disease indifference and more knowledge to feelings of anguish / fear and altruism. In response to the question about which disease was the most feared, leprosy was mentioned by 8.06% of the students being the fourth worst. The fact that it was the worst disease mentioned was related to the higher knowledge index. It is worrying that more than 30% of the students who live in a former colony area have never heard about the disease, once it is part of the place’s history or of the individual himself. It is suggesting that there is a silence on the topic that can be both cause and consequence of stigma and prejudice and can make it difficult to control the disease. The work has limitations, the biggest of is the fact that it uses a database that was not obtained for research and had no criteria for random sampling. However, the results point to the need to invest in health education about leprosy in colonies areas, not only to combat stigma and prejudice, but as a measure of epidemiological surveillance.